Photobiology of the giant kelp Macrocystis pyrifera in the land-terminating glacier fjord Yendegaia (Tierra del Fuego): A look into the future? - Palacios, Mauricio; Osman, Dayane; Ramirez, Jaime; Huovinen, Pirjo; Gomez, Ivan (My University, 2021)
The channel and fjord region of southern Chilean Patagonia hosts giant kelp forests (Macrocystis pyrifera) that have little known site -specific responses to diverse physical gradients. In this study, the functionality of the bio-optical, morphological and biochemical features of the kelps, that determine their light trapping and acclimation, were studied along a gradient of varying turbidity and light conditions at the land-terminating glacier of fjord Yendegaia in the Beagle Channel. These habitats are marked by glacial retreat, and M. pyrilem has successfully colonized new areas due to the effects of warming. Results indicated that under a sharp gradient of turbidity and light availability, the kelps have adapted shading characteristics. The photobiological traits (e.g. light absorption, pigment concentration, photochemistry and blade optics) of algae from depths between 6 and 13 m varied in relation to the degree of turbidity along the fjord. However, these populations did not show obvious intrathallus variation along the longitudinal profile e.g. blades located at different depths showed relatively similar acclimation potential to the prevailing light field. Only basal sporophylls showed general differences in comparison with the vegetative fronds. Otherwise, the high phenolic (phlorotannin) content, which was reflected in the massive presence of intracellular physodes, suggests that these organisms could be biochemically well-equipped to cope with changes in physical conditions or the presence of herbivore invertebrates (e.g. sea urchins). (C) 2020 Elsevier B.V. All rights reserved.
Keywords: giant kelp; southern patagonian fjord; photosynthesis; turbidity; blade bio-optics